Pengaruh Pertumbuhan Ekonomi Dan Tingkat Upah Terhadap Tingkat Pengangguran Melalui jumlah Investasi Di Provinsi Bali - Mentari, Ni Wayan; Mahaendra Yasa, I Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 6, Juni 2016 (pp. 652-728), 2016)
The unemployment in the district/city in Bali is uneven. It is caused by the imbalance of economic growth, wage levels and the investment between the regions on the district/city in Bali. This research aimed to analyze the direct and indirect effect of the economic growth and wage levels on the unemployment through the intervening variable of investment in the district/city in the province of Bali. The data are used in this research’s data time series for five years from 2009 to 2013 and cross section data for as many as nine counties/cities in the province of Bali. The analysis of the data that used in this research’s by the path analysis. The results of the analysis shows that economic growth and wage levels is positive and significant effect on the amount of the investment. Economic growth is negative and significant effect, while the wage levels and the investment amount is a positive and significant effect on the unemployment. The effect of economic growth and wage is indirectly and significantly on the unemployment through the investment as the intervening variable.
Keywords: economic growth; wage levels; investment; unemployment